The Explanatory Study of China's Iron and Steel Industry Competitiveness in The Developmental State Theory - Hakim, Amri; Suryaningsih, Suryaningsih (Jurnal Ilmiah Ekotrans & Erudisi, 2025)
The low technological and energy efficiency of China's iron and steel industry is not directly correspond with the competitiveness of its products in both domestic and international markets. This study aims to explain the anomaly of the high competitiveness of China's iron and steel industry despite its low production efficiency. Using developmental state theory  and qualitative methods, it was found that the Chinese Government sets the direction of development and increasing the competitiveness of its iron and steel industry in every five-year development plan. The government also affects the supply side with protection policies. To compensate the production inefficiencies, the Chinese government provides direct, and indirect, also structural subsidies. On the demand side, the government makes stimulus projects and opens foreign markets through regional free trade agreements that make high economies of scale which decreasing production cost.